Book of the Songs of Israel : Three Introductions to Psalms on Poetry, Translation, and Music by Joel Bril (Berlin 1791). A Bilingual Edition, translated with Commentary and an Introduction - Sela Teichler, Yael, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
This annotated bilingual edition presents to readers for the first time a key Hebrew book of Jewish Enlightenment. Printed in Berlin in 1791, Joel Bril's Hebrew introductions to Psalms constitute the earliest interpretation of Moses Mendelssohn's language philosophy, translation theory, and aesthetics. In these introductions, Mendelssohn emerges as a critic of Maimonides who located eternal felicity not in union with the Active Intellect but in the aesthetic experience of the divine through sacred poetry. Bril's theoretical insights, the broad range of his myriad textual sources, and his linguistic innovations make the Book of the Songs of Israel a touchstone of modern Hebrew literary theory and Jewish thought. See Less